Students' Speaking Skills Using Digital Story Telling Media At The University Level - Darningwati, Darningwati; Ramadhaniati, Ratih Utami (Universitas Muria Kudus, 2025)
The purpose of this study is to describe the speaking skills of third semester students of the Indonesian Language and Literature Education Study Program using digital storytelling media. And describe what factors influence the ability of third semester students of the Indonesian Language and Literature Education Study Program using digital storytelling media. The method used in this study is a descriptive method. The population in this study were 45 third semester students of the Indonesian Language and Literature Education Study Program. The sample in this study was all 45 third semester students of the Indonesian Language and Literature Education Study Program. The research method is a descriptive method. Based on the results of the analysis of the abilities of third semester students of the Indonesian Language and Literature Education Study Program in this study, the average score was 75.66 in speaking using digital storytelling media. This can be interpreted that third semester students have the category of being able to speak using digital storytelling media.